Investigating the awareness, attitude and performance of kindergarten teachers towards social harms and children's abuse - Kashani Movahed, Bahareh; Hosseinian Serajehloo, Faraj; Rashedi, Roza; Ganji, Nima (Journal of Psychosociological Research in Family and Culture, 2023)
Child abuse is a widespread social phenomenon with life-long severe consequences. Kindergarten teachers can follow up on this issue by constantly interacting with children and families in case of family dysfunction. This study investigated the knowledge, attitude and performance of kindergarten teachers in Tehran in 2022. The current study was descriptive; the statistical population included all kindergarten teacher certificate holders from the welfare organization. Subjects were selected by stratified (random) sampling from educational centers for kindergarten teacher courses under the supervision of welfare organizations that had received certificates. The sample size was 350 people, and the data collection tool was a questionnaire. The data was analyzed with SPSS version 22 software. The findings showed that the knowledge and awareness of 66.9% of the teachers regarding misbehaving with a good child and the attitude of 54.9% of them are at the desired level. Also, the performance of 88.1% of them in facing child abuse was poor and average. The results of this study showed that kindergarten teachers had a good knowledge of child abuse, a favorable attitude toward dealing with child abuse, and a poor performance in dealing with child abuse. The weak performance may be due to fewer training courses, fear of marginal issues of dealing with child abuse, or the lack of clear legal guidelines for dealing with child abuse.